Penyebaran Nilai-Nilai Ideologis Kelompok Minoritas Muslim: Kajian atas Jamaah Tabligh Wonosobo, Jawa Tengah - Siti Khodijah Nurul Aula; Derry Ahmad Rizal; Nur Afni Khafsoh (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2022)
The presence of minority groups always presents dynamics in society. The Tablighi Jamaat has so far been classified as a religious minority group from among Muslims. As a minority group, the presence of the Tablighi Jamaat creates dynamics and conflict in the neighborhood where they live. This article aims to explain the forms and strategies in conveying the values of the religious ideology of the Muslim minority group Jamaah Tabligh in Tambi village, Wonosobo, Central Java to the surrounding community. The data used as the basis for the analysis were obtained through observation, interviews, and literature review. This article shows that the process of spreading ideological values carried out by the Tablighi Jamaat in Wonosobo was carried out based on the texts fadholilul amal, six characteristics of a friend, and khuruj fi sabilillah. Meanwhile, the efforts made by the Tablighi Jamaat group to be accepted in society through a number of things, such as: fighting the stigmatization of post-ijtima 'ulama in Gowa, South Sulawesi, carrying out a distinctive and consistent da'wah strategy, and cultural acculturation. In the face of rejection by the community, the solution chosen by the Tablighi Jamaat is to seek legitimacy for their actions through the text of fadholilul amal, the central emir, and other fellow followers of the Tablighi Jamaat. This article is still limited to the practice of spreading ideological values from the teachings of the Tablighi Jamaat in the village of Tambi, Wonosobo, so there is still a need for studies on similar Muslim minority groups in various regions in Indonesia.